<h3><u>Given Information :</u></h3>
- Length of parallel sides = 60 ft and 40 ft
- Height of the trapezoid = 30 ft
<h3><u>To calculate :</u></h3>
<h3><u>Calculation :</u></h3>
As we know that,
![\bigstar \: \boxed{\sf {Area_{(Trapezium)} = \dfrac{1}{2} \times ( a + b) \times h}} \\](https://tex.z-dn.net/?f=%5Cbigstar%20%5C%3A%20%5Cboxed%7B%5Csf%20%7BArea_%7B%28Trapezium%29%7D%20%3D%20%5Cdfrac%7B1%7D%7B2%7D%20%5Ctimes%20%28%20a%20%2B%20b%29%20%5Ctimes%20h%7D%7D%20%5C%5C%20)
- a and b are length of parallel sides.
- h denotes height.
<em>S</em><em>u</em><em>b</em><em>s</em><em>t</em><em>i</em><em>t</em><em>u</em><em>t</em><em>i</em><em>n</em><em>g</em><em> </em><em>valu</em><em>es</em><em>,</em><em> </em><em>we</em><em> </em><em>get</em><em> </em>:
Area =
× ( 60 + 40 ) × 30 ft![\sf ^2](https://tex.z-dn.net/?f=%20%5Csf%20%5E2%20)
Area =
× 100 × 30 ft![\sf ^2](https://tex.z-dn.net/?f=%20%5Csf%20%5E2%20)
Area = 1 × 100 × 15 ft![\sf ^2](https://tex.z-dn.net/?f=%20%5Csf%20%5E2%20)
Area = 100 × 15 ft![\sf ^2](https://tex.z-dn.net/?f=%20%5Csf%20%5E2%20)
<u>Area = 1500 ft</u>![\sf ^2](https://tex.z-dn.net/?f=%20%5Csf%20%5E2%20)
Therefore,
- Area of the trapezoid is <u>1500 ft
</u>
Answer:
the answer should be c.
Step-by-step explanation:
here's why....A uses 4 more which is adding. B uses 4 fewer which is subtracting and D does not complete so it should be C.
Answer:
![e^x+xy+3y+(y-1)e^y=4](https://tex.z-dn.net/?f=e%5Ex%2Bxy%2B3y%2B%28y-1%29e%5Ey%3D4)
Step-by-step explanation:
Given that
![(e^x+y)dx+(3+x+ye^y)dy=0](https://tex.z-dn.net/?f=%28e%5Ex%2By%29dx%2B%283%2Bx%2Bye%5Ey%29dy%3D0)
Here
![M=e^x+y](https://tex.z-dn.net/?f=M%3De%5Ex%2By)
![N=3+x+ye^y](https://tex.z-dn.net/?f=N%3D3%2Bx%2Bye%5Ey)
We know that
M dx + N dy=0 will be exact if
![\frac{\partial M}{\partial y}=\frac{\partial N}{\partial x}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cpartial%20M%7D%7B%5Cpartial%20y%7D%3D%5Cfrac%7B%5Cpartial%20N%7D%7B%5Cpartial%20x%7D)
So
![\frac{\partial M}{\partial y}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cpartial%20M%7D%7B%5Cpartial%20y%7D%3D1)
![\frac{\partial N}{\partial x}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cpartial%20N%7D%7B%5Cpartial%20x%7D%3D1)
it means that this is a exact equation.
![\int d\left(e^x+xy+3y+(y-1)e^y\right)=0](https://tex.z-dn.net/?f=%5Cint%20d%5Cleft%28e%5Ex%2Bxy%2B3y%2B%28y-1%29e%5Ey%5Cright%29%3D0)
Noe by integrating above equation
![e^x+xy+3y+(y-1)e^y=C](https://tex.z-dn.net/?f=e%5Ex%2Bxy%2B3y%2B%28y-1%29e%5Ey%3DC)
Given that
x= 0 then y= 1
![e^0+0+3+(1-1)e^1=C](https://tex.z-dn.net/?f=e%5E0%2B0%2B3%2B%281-1%29e%5E1%3DC)
C=4
So the our final equation will be
![e^x+xy+3y+(y-1)e^y=4](https://tex.z-dn.net/?f=e%5Ex%2Bxy%2B3y%2B%28y-1%29e%5Ey%3D4)